Communication of Kato Nan Ampek Cultural Perspective in Minangkabau Community in Medan Denai District, Medan City - Irfan Ar Chaniago; Muhammad Alfikri (PT Mattawang Mediatama Solution, 2022)
The goal of this study was to discover how the kato nan ampek cultural perspective communication was applied to the Minangkabau community in Medan Denai District, Medan City. This is a qualitative study that employs the descriptive method. During the research, it was discovered that the community, particularly the older Minangkabau generation, continued to use the communication procedures governed by the kato nan ampek concept. However, the younger generation does not fully appreciate the value of kato nan ampek. Furthermore, there has been a shift in the use of various Minangkabau language greeting words, with the younger generation preferring foreign language greeting words over their native language greeting words. Parental and environmental factors contribute to the decline of kato nan ampek cultural values in the Minangkabau younger generation. The formation of adolescent behavior with mutual cooperation is an effort to increase the value of kato nan ampek in the younger generation.